MODERN DIMENSION OF TASKS OF THE SCIENTIFIC ORGANIZATION OF THE EDUCATIONAL PROCESS OF TRAINING OF TEACHERS OF FINE ARTS IN THE SYSTEM OF ARTISTIC AND ARTISTIC (Pedagogy of Higher and Secondary Education, 2022)
The urgent problems of scientific organization of educational process of préparation of the teachers of fine arts in system of art-pedagogical éducation on Ukraine are considered and the experience of job in this direction of art graphic faculty о/ the South-Ukrainian pedagogical university.